Rapid immunoassay exploiting nanoparticles and micromagnets: proof-of-concept using ovalbumin model. (March 2017) - Delshadi, Sarah; Blaire, Guillaume; Kauffmann, Paul; Fratzl, Mario; Devillers, Thibaut; Delabouglise, Didier; Weidenhaupt, Marianne; Dempsey, Nora M; Cugat, Orphée; Bruckert, Franz; Marche, Patrice N
Aim: We present a fast magnetic immunoassay, combining magnetic nanoparticles and micromagnets. High magnetic field gradients from micromagnets are used to develop a new approach to the standard ELISA.Materials & methods/results: A proof-of-concept based on colorimetric quantification of antiovalbumin antibody in buffer is performed and compared with an ELISA. After optimization, the magnetic immunoassay exhibits a limit of detection (40 ng/ml) and a dynamic range (40–2500 ng/ml) similar to that of ELISAs developed using same biochemical tools.Conclusion: Micromagnets can be fully integrated in multiwell plates at low cost to allow the efficient capture of immunocomplexes carried by magnetic nanoparticles. The method is generic and permits to perform magnetic ELISA in 30 min.